Evaluation of Trichospilus diatraeae (Hymenoptera: Eulophidae) as parasitoid of the eucalyptus defoliator Euselasia eucerus (Lepidoptera: Riodinidae). - Zache, Bruno [UNESP]; Zache, Ronelza Rodrigues da Costa [UNESP]; Soliman, Everton Pires [UNESP]; Wilcken, Carlos Frederico [UNESP] (Springer Nature, 2011)
Lepidopteran pests have occurred in eucalyptus plantations in Brazil since 1948, reaching high population levels, reducing tree growth and causing considerable losses in wood production. The control of defoliating caterpillars in eucalyptus forests is complex, mainly due to the large extent of forest plantations and tree height, necessitating the aerial application of chemical or biological insecticides. Due to this complexity, alternative control methods have been proposed, for instance biological control through the use of parasitoids. Trichospilus diatraeae Cherian & Margabandhu, 1942 is a gregarious pupal parasitoid that preferentially attacks species of the order Lepidoptera. This is the first report of T. diatraeae parasitizing pupae of the eucalyptus defoliator Euselasia eucerus Hewitson in Brazil. This parasitoid offers new perspectives for the biological control programmes of this species in eucalyptus plantations in Brazil.